Islamic factor in policy of the Soviet government and the provision of Islam in Kazakhstan - Aktaulova, B. (Journal of Oriental Studies, 2016)
in this article the author considers a problem of an islamic factor in domestic and foreign policy of the soviet government, and also the the provision of islam in Kazakhstanduring the soviet period. the author analyzes methods of policy of the soviet government concerning islam during the evolutionary periods of history of the soviet Union and in particular Kazakhstan.